Written-Pole Motor – A Mini Review - Ranadev, Manjunath B.; Chakrasali, Ramesh L. (Applications of Modelling and Simulation, 2020)
Electrical motors are used as drives in most of the industries. There is a progress in electrical motor technology in terms of design, new materials and performance characteristics based on the applications. The written pole motor is yet another alternative for certain specific applications. In this paper, an attempt is made to review the principle of operation, constructional features, operating characteristics, applications of written pole motor along with cost. The written pole motors permit flexible load available on an electric utility. It easily accelerates back to synchronism without excessive inrush current after a short power interruption even at rated load. These motors assure quality power and ride through from utility sags and surges. The motors also avoid harmonics of higher order. The discussion presented here also includes the protection to the utility consumer from reclosure and other operation for reliable utility operation. The paper highlights the potential application areas at present and future trends.